WA’A CO’I UMA SEBAGAI SYARAT PERKAWINAN DALAM PERSPEKTIF HUKUM ISLAM (STUDI ANALISIS PANDANGAN TOKOH MASYARAKAT DESA PALAMA KECAMATAN DONGGO KABUPATEN BIMA) - Muhammad, Hidayatullah (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2019)
The researcher wants to examine the parts of Indonesian culture and traditions, which in practice require that they provide a house or wa'a co’i uma. The village of Palama Kec Donggo, Kabupaten Bima, which is the location of this thesis research, has a different stage of marriage from other regions, the problem now is for the community of middle-class economies with wa'a co'i uma dowry that leaves no problems and is acceptable happily, but for them the lower middle class is problematic. What if they were eager to get married and be able to be religiously and legally lawful, but not able to fulfill the traditional laws of this research. The aim of this study was to find out the tradition of giving wa'a co'i uma as a marriage requirement in Palama village, Kec. the views of community leaders about the surrender of wa'a co'i uma as a marriage requirement in the village of Palama Kec Donggo Kabupaten Bima, to find out in depth the review of Islamic law towards wa'a co'i uma as a condition of marriage in Palama village, Kec. Donggo, Bima. The approach in this study is a qualitative method with a type of case study research, a research site in Palama Village, Donggo Subdistrict, Bima Regency, with research subjects as maysarakat figures, Palama Village, Kec Hemat Donggo, Bima Regency. The results of this study include two parts: First, Preparation, Both Applications, this includes several stages: Stages Wi'i Ngahi or Panati, StagesDou Sodi, Tahapan Mbolo Weki, StagesWa'a Coi, StagesTeka Ra Ne'e, and the last stage of the marriage contract.These stages determine the implementation of adat in the implementation of marriages in the village of Palama.